A meta-analysis and systematic review of myocardial infarction-induced cardiomyocyte proliferation in adult mouse heart - Ya Liu; Lingyan Liu; Pengcheng Zhuang; Jiamin Zou; Xiaokang Chen; Hao Wu; Bingjun Lu; Wei Eric Wang (BMC Medicine)
Abstract Background The proliferation capacity of adult cardiomyocytes is very limited in the normal adult mammalian heart. Previous studies implied that cardiomyocyte proliferation increases after injury stimulation, but the result is controversial partly due to different methodologies. We aim to evaluate whether myocardial infarction (MI) stimulates cardiomyocyte proliferation in adult mice. Methods A comprehensive literature search was conducted through PubMed/Medline, Embase, and Web of Science databases from 1 January 2000 to 21 December 2023. The SYRCLE’s Risk of Bias tool for animal experiments was used to evaluate the quality of the literature by two independent reviewers. Twenty-six studies with cell cycle indicators (Ki67+, PH3+, BrdU/EdU+, and AurkB+) to evaluate cycling cardiomyocytes were collected for a meta-analysis. Another 10 studies with genetic reporter/tracing systems to evaluate cardiomyocyte proliferation were collected for a systematic review. Results Evaluating cardiomyocyte proliferation by immunostaining of the cell cycle indicators on heart tissue, the meta-analysis showed that differences of Ki67+, PH3+, and BrdU/EdU+ cycling cardiomyocytes between MI and Sham groups were not statistically significant. In the post-MI heart, the percentages of PH3+, BrdU/EdU+, and AurkB+ cardiomyocytes were not significantly different between the infarct border zone and remote zone. The percentage of Ki67+ cardiomyocytes in the infarct border zone was statistically higher than that in the remote zone. Most of the studies (6 out of 10) using genetic reporter/tracing mouse systems showed that the difference in cardiomyocyte proliferation between MI and Sham groups was not statistically significant. Among the other 4 studies, at least 3 studies could not demonstrate that MI stimulates bona fide cardiomyocyte proliferation because of methodological shortages. Conclusions MI injury increases Ki67+ cycling adult mouse cardiomyocytes in infarct border zone. Very little overwhelming evidence shows that MI stimulates bona fide proliferation in the adult heart. Graphical Abstract